Performance measurement and management control contemporary issues - Epstein, Marc J.; Verbeeten, Frank; Widener, Sally K. (Sally Kathryn) (Studies in managerial and financial accounting ;, 2016)
Volume 31 of Studies in managerial and financial accounting (SMFA) covers contemporary issues in performance measurement and management control.These papers are taken from 8th Conference on performance measurement and management control 2015. The topic of this edition is contemporary issues in performance measurement and management control. This is a broad topic by design with the intent of reporting on important research and issues relevant today. For example, papers in the book explore the following: Performance measurement and management control in emerging markets; the use of social and or informal controls; Linkages between creativity, innovation, and control; Innovative control practices in healthcare; Behavioral effects of alternative incentive schemes; Performance evaluation for different organizational designs; Performance measurement in high-performing firms.